Action Choice and Outcome Congruency Independently Affect Intentional Binding and Feeling of Control Judgments - Barlas, Zeynep; Kopp, Stefan (Frontiers in Human Neuroscience, 2018)
Sense of agency (SoA) refers to the subjective experience that one is in control of their actions and the consequences of these actions. The SoA is a complex phenomenon, influenced by a weighted combination of various prospective (pre-movement) and retrospective (post-movement) processes and factors related to action choice, action selection fluency, action-outcome associations, and higher-level inferences. In the current study, we examined the effect of the congruency between actions and outcomes in a context where the choice-level of actions was varied from one to four. The actions consisted of right, left, up, and down key presses while the outcomes were visual representations of the actions (i.e., right, left, up, and down-pointing arrowheads). Participants performed either an instructed action or freely selected an action among two, three, or four alternatives. Each action randomly produced either a congruent or an incongruent outcome, depending on the matching between the direction of the key press and the direction of the outcome arrowhead. Participants estimated the delay between their actions and the observed outcomes and reported their feeling of control (FoC) over the outcomes. Interval estimations were used as an indirect measure of the SoA to quantify the intentional binding effect, which refers to the perceived temporal attraction between voluntary actions and their outcomes. The results showed that both intentional binding and FoC were enhanced as the choice-level was increased from one to four. Additionally, intentional binding and FoC over the outcomes were stronger when actions produced congruent compared to incongruent outcomes. These results provide additional evidence that both intentional binding and FoC are sensitive to the number of action alternatives and the congruency between actions and their outcomes. Importantly, the current study suggests that these prospective and retrospective cues might independently influence intentional binding and FoC judgments.